Over-the-scope-clip treatment of gastrobronchial fistula following minimally invasive oesophagectomy: a novel approach. Issue 8 (12th August 2019) - Kordzadeh, Ali; Syllaios, Athanasios; Davakis, Spyridon; Lorenzi, Bruno; Jayanthi, Naga V; Tang, Cheuk-Bong; Charalabopoulos, Alexandros
ABSTRACT: Gastrobronchial fistulae (GBF) following minimally invasive oesophagectomy (MIO) is a rare entity, with an estimated incidence of 0.3–1.5% according to the published literature. It could present with persistent cough (Ohno's sign), chest pain, haemoptysis and recurrent pneumonia. Barium swallow examination remains the most sensitive investigation in 78% of the cases; the main stay of management is surgical and in some cases endoscopic (stent insertion). We report a rare case of a GBF 1 month after two-stage MIO for cancer of the gastro-oesophageal junction, which was successfully treated for the first time with an over-the-scope-clip.